A lanthanide(iii) metal–organic framework exhibiting ratiometric luminescent temperature sensing and tunable white light emission. Issue 23 (1st March 2016) - Wu, Lan-Lan; Zhao, Junfang; Wang, Hui; Wang, Jingyuan
Abstract : New lanthanide(iii ) metal–organic frameworks are constructed and exhibit a good linear relationship with respect to the temperature range of 75–250 K. White light emission can be realized by varying the excitation wavelength ofEu 0.0748 Tb 0.9252 L . Abstract : A new lanthanide(iii ) metal–organic framework was constructed as well as the co-doped compounds. The ratiometric luminescent thermometerEu 0.0878 Tb 0.9122 L exhibits a good linear relationship with respect to the temperature range of 75–250 K. White light emission can be realized by varying the excitation wavelength ofEu 0.0748 Tb 0.9252 L .